Multi-stage hashing network storage structure for intelligent routing - Feng ZHU; Qun HUANG (Dianxin kexue)
Network data collection and storage are fundamental for intelligent routing control,providing massive flow data for model training and decision-making.However,as the key device in network storage system,switches have very limited memory size and design flexibility,which can’t satisfy the needs of intelligent routing control for comprehensive high-precision data and lightweight storage system,thus reducing the effectiveness of intelligent routing control.A multi-stage hashing network storage structure (MHNSS) was proposed for intelligent routing control,which fully utilized the limited memory resource of switch and completed network data storage with low collision rate.The number of candidate buckets of the flow key was augmented by multi-stage hash table,thus reducing collision rate and improving memory load ratio.Hash collision was resolved via coarse-grained timestamp LRU algorithm,which always stored most recently used data and cleared least recently used data to avoid subsequent collisions as far as possible.Trace-driven experiments showed that compared with widely used single hash table,MHNSS had significant performance advantage in collision rate and load ratio.